Gambaran Epidemiologi Kasus Leukemia Anak di Rumah Sakit Kanker âDharmaisâ, 2004-2008 - SIMANJORANG, CHANDRAYANI; ADISASMITA, ASRI; TEHUTERU, EDI (Indonesian Journal of Cancer, 2010)
This current study describes epidemiology of leukemia among children seeking care to Dharmais cancer hospital in the year 2004-2008. This is a case series study using primary and secondary data. Result showed the highest proportion of death was found among cases with AML leukemia, followed by patients with high risk ALL cases, and those who were refered. The older the age at first diagnosis, the smaller the probability to survive among children with leukemia, in general.